Measurement of the electrokinetic properties of peats treated with chemical solutions - Moayedi, Hossein; Nazir, Ramli; Kassim, Khairul Anuar; Kim Huat, Bujang (Elsevier, 2014)
In this study the relations between different chemical stabiliser solutions on the electrokinetic (EK) properties of tropical peat such as surface charge, diffuse double layer (DDL), current density, electroosmosis flow (EOF) and energy consumption are measured. The EK injection tests (with different chemical solutions) were performed with several electrolytes, namely, sodium silicate (Na2SiO3), calcium oxide (CaO), aluminium hydroxide (Al(OH)3) and calcium chloride (CaCl2) as chemical reagents. As a result, the suspensions with the high molarities of CaCl2, Al(OH)3 and CaO caused colloidal charge reversal in the surface of the colloidal from the negative to the positive. Furthermore, for the injection of NS-DW solution through the peat, electrokinetically, the total required energy was higher, about 693%, 373% and 234% for the EK injection of Al-DW, CaO-DW and Ca-DW, respectively. The same trend was also measured for the current density. After three days of EK tests, the current density for Al-DW, CaO-DW, Ca-DW and NS-DW was 0.267, 0.401, 0.668 and 1.872 mA/cm2, respectively. The results of this research can be used to evaluate an initial estimation for required energy to inject electrically and changing the flow net in a real elektrokinetic treatment.